Multisegmented nanotubes by surface-selective atomic layer deposition - Bae, Changdeuck; Zierold, Robert; Moreno, Josep M. Montero; Kim, Hyunchul; Shin, Hyunjung; Bachmann, Julien; Nielsch, Kornelius (Journal of Materials Chemistry C, 2013)
We describe a general strategy for fabricating multisegmented nanotubes and nanopores via sequential, surface-selective modification with organic and inorganic layers combined with in situ formation of nanopores by electrochemical anodization. We found that cylindrical alumina nanopores can be continuously anodized upon coating thin organic and/or inorganic layers such as octadecyltrichlorosilane (OTS)-self-assembled monolayers (SAMs), and atomic layer deposition (ALD)-grown TiO2, ZnO, and ZrO2, allowing for three-dimensionally site-selective ALD. As model systems, we show that (1) isolated metal oxide nanotubes can be prepared as-grown with controlled opening at the distal ends of tubes, (2) inner surfaces of nanopores can be chemically and physically modified in a segmented manner, and (3) a nanotube core-multisegmented shell geometry can be achieved. We believe that the present approach will open up new avenues for realizing complex nanodevices such as nanofluidic diodes, photovoltaic junctions, and transistors by adding a degree of freedom in the synthesis of nanotubes/pores in their axis direction.